2005
DOI: 10.1128/aem.71.8.4761-4770.2005
|View full text |Cite
|
Sign up to set email alerts
|

Nonpathogenic Strains ofColletotrichum lindemuthianumTrigger Progressive Bean Defense Responses during Appressorium-Mediated Penetration

Abstract: The fungal bean pathogen Colletotrichum lindemuthianum differentiates appressoria in order to penetrate bean tissues. We showed that appressorium development in C. lindemuthianum can be divided into three stages, and we obtained three nonpathogenic strains, including one strain blocked at each developmental stage. H18 was blocked at the appressorium differentiation stage; i.e., no genuine appressoria were formed. H191 was blocked at the appressorium maturation stage; i.e., appressoria exhibited a pigmentation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…Of note, Cgstimulated PEN2, PEN3, CYP79B2, and CYP81F2 expression was detectable even earlier, at 9 hpi ( Figure 5A), indicating that Arabidopsis perceives the attack on the leaf surface and mounts defense responses to the intruder prior to the initiation of invasive growth. This is consistent with previous work on nonpathogenic Colletotrichum lindemuthianum mutant strains, showing that on leaves of its host, Phaseolus vulgaris, the formation of nonfunctional appressoria (i.e., failure to grow inside plant cells) was sufficient to induce plant defense responses (oxidative burst and PR protein accumulation; Veneault-Fourrey et al, 2005).…”
Section: Discussionsupporting
confidence: 81%
“…Of note, Cgstimulated PEN2, PEN3, CYP79B2, and CYP81F2 expression was detectable even earlier, at 9 hpi ( Figure 5A), indicating that Arabidopsis perceives the attack on the leaf surface and mounts defense responses to the intruder prior to the initiation of invasive growth. This is consistent with previous work on nonpathogenic Colletotrichum lindemuthianum mutant strains, showing that on leaves of its host, Phaseolus vulgaris, the formation of nonfunctional appressoria (i.e., failure to grow inside plant cells) was sufficient to induce plant defense responses (oxidative burst and PR protein accumulation; Veneault-Fourrey et al, 2005).…”
Section: Discussionsupporting
confidence: 81%
“…Melanized appressoria of M. oryzae accumulate solutes with an osmotic potential of up to 8.0 MPa, which is 30 to 70% higher than in appressoria of melanin-deficient mutants of this fungus (Dean 1997). Similarly, nonmelanized appressoria of C. lindemuthianum showed cell collapse at much lower osmolyte concentrations than melanized appressoria (Veneault-Fourrey et al 2005).…”
Section: Discussionmentioning
confidence: 93%
“…Rapid accumulation of ROS by the host, which was observed beneath the appressorial structures, is apparently caused by local mechanical pressure generated by the developing appressoria. In C. lindemuthianum , it was shown that appressorium maturation, but not function, is sufficient to induce most plant defence responses (Veneault‐Fourrey et al ., 2005). The presence of abundant ROS produced by the host to account for penetration failure has also been observed for Colletotrichum coccodes causing anthracnose disease in tomato.…”
Section: Discussionmentioning
confidence: 99%